Physical condition and reproductive behavior of captive Malayan pangolin, Manis javanica - Chai, Siew Ying (2011)
The aim of this study was to investigate the activity pattern and physical condition of pangolins Manis javanica during pregnancy, in the period of maternal care and to also propose suitable captive management strategies. Two subjects were studied; one was in her third trimester of pregnancy the other in the period of post pregnancy. During the post pregnancy period more diurnal activity was observed and the overall level of activity was higher. Certain behavior states like pausing and drinking were more apparent in pangolins exhibiting maternal care. Activity patterns on the first half of the day were similar between both subjects with peak activity at 22:00 hr. Weekly body condition indices calculated for a period of five weeks showed that the subject in post pregnancy was in good condition. There was little evidence in relationship between temperature, humidity and level of pangolin activity. Suggestions to captive management of pregnant pangolins include heat lamps in the dens to maintain interior temperature at 27 to 29 ̊C, and feeding on alternate days.